Agile governance and audit : an overview for auditors and agile teams - Wright, Christopher (Accountant) (IT Governance Pub., 2014)
This book bridges the gap between traditional auditing approaches and the requirements of Agile methodologies. It provides an overview of Agile for auditors and other risk professionals who have not encountered the approach before. The book also tells Agile teams what auditors and risk professionals need, and the sort of questions they are likely to ask. Essential reading for anyone involved in an Agile audit: Each chapter includes hints and tips for auditors, and a selection of case studies is included to illustrate the practical issues involved in auditing Agile projects. This makes it an ideal book for any auditor encountering the Agile methodology, and any Agile teams preparing for a management audit. This book will enable you to: understand the principles of Agile; appreciate how it might be effectively audited; improve communication between the auditor and the Agile team. --